ω – SUBSEMIRING FUZZY - Saman Abdurrahman (Jurnal Matematika Sains dan Teknologi, 2020)
Mapping ρ is called a fuzzy subset of an empty set of S if ρ is the mapping from S to the closed interval [0,1]. A fuzzy subset ρ introduced into this paper is a fuzzy subset of semiring S, defined byρ(a+d)≥ρ(a)∧ρ(d) and ρ(ad)≥ρ(a)∧ρ(d),for each a,d∈S so that a fuzzy subset ρ is called a fuzzy subsemiring from a semiring S.In this paper, Investigated the basic nature of subsemi-ring fuzzy ρ from a semiring S, which includes intersecting with two or more fuzzy subsemiring from a semiring S, is always a fuzzy subsemiring from a semiring S. Moreover, it was introduced to the concept of ω – fuzzy subsemiring from a semiring S which is denoted by ρω. Finally, investigated the minimal conditions that guarantee the existence of ω – fuzzy subsemiring ρω and the intersection of two or more ω – fuzzy subsemiring ρω of a semiring, S is always an ω – fuzzy subsemiring ρω of a semiring S. Pemetaan disebut subset fuzzy dari himpunan tidak kosong jika merupakan pemetaan dari ke interval tutup . Subset fuzzy yang diibahas pada paper ini adalah subset fuzzy dari semiring , yang memenuhi kondisi dan , untuk setiap sedemikian sehingga subset fuzzy disebut subsemiring fuzzy dari semiring . Pada paper ini, diselidiki sifat dasar dari subsemiring fuzzy dari semiring , yang meliputi irisan antara dua atau lebih subsemiring fuzzy dari semiring selalu merupakan subsemiring fuzzy dari semiring . Selain itu, pada paper ini diperkenalkan konsep – subsemiring fuzzy dari semiring , yang dinotasikan dengan . Akhirnya, diselidiki kondisi minimal yang menjamin eksistensi dari – subsemiring fuzzy , dan irisan dua atau lebih – subsemiring fuzzy dari semiring selalu merupakan – subsemiring fuzzy dari semiring .